Receptor-mediated endocytosis of asialoglycoproteins by rat hepatocytes: receptor-positive and receptor-negative endosomes (The Rockefeller University Press, 1986)
We have used combinations of subcellular fractionation, specific cytochemical tracers, and quantitative immunoadsorption to determine when, where, and in which intracellular structure internalized asialoglycoproteins (ASGPs) are segregated from their receptor. All membrane vesicles containing the receptor (R+ vesicles) were quantitatively immunoadsorbed from crude microsomes with Staphylococcus aureus cells and affinity-purified anti-ASGP receptor. Using this assay, we varied the time and temperature of exposure of perfused livers to 125I-asialoorosomucoid (125I-ASOR) and followed the movement of ligand from R+ to R- vesicles. After 2.5 min at 37 degrees C, 98% of the internalized ligand could be immunoadsorbed and thus was in R+ vesicles. Over the next 12 min of continuous 37 degrees C perfusion with 125I-ASOR, an increasing fraction of the ligand was not immunoadsorbed and therefore was present in R- vesicles. A maximum of 30% of the ligand could be found in R- vesicles (14-44 min). When livers were maintained at 16 degrees C, ligand was internalized but remained in R+ vesicles. Furthermore, ligand accumulating in R- vesicles at 37 degrees C remained there when livers were cooled to 16 degrees C. R- endosomes could be separated from R+ endosomes by flotation on sucrose density gradients and visualized by the presence of sequestered ASOR-horseradish peroxidase (ASOR-HRP). These structures resembled those labeled by ASOR-HRP in situ: R+ vesicles were relatively dense (1.12 g/cc), frequently tubular or spherical and small (100-nm diam), corresponding to the peripheral and internal tubular endosomes; R- structures were of lower density (1.09 g/cc), large (400- nm diam), and resembled internal multivesicular endosomes (MVEs). Endocytosed ASOR-HRP was found in both the peripheral and internal tubular endosomes in situ under conditions where 95% of the ligand was present in R+ vesicles by immunoadsorption, whereas MVEs containing ASOR-HRP were predominant in situ when ligand was found in R- vesicles and were often in continuity with the tubular internal endosomes. All of these results suggest that complete segregation of ligand and receptor occurs after arrival in the Golgi-lysosome region of the hepatocyte and that MVEs are R- and represent the final prelysosomal compartment.